AMPK is activated during lysosomal damage via a galectin-ubiquitin signal transduction system. Issue 8 (2nd August 2020) - Jia, Jingyue; Bissa, Bhawana; Brecht, Lukas; Allers, Lee; Choi, Seong Won; Gu, Yuexi; Zbinden, Mark; Burge, Mark R.; Timmins, Graham; Hallows, Kenneth; Behrends, Christian; Deretic, Vojo
ABSTRACT: Lysosomal damage activates AMPK, a regulator of macroautophagy/autophagy and metabolism, and elicits a strong ubiquitination response. Here we show that the cytosolic lectin LGALS9 detects lysosomal membrane breach by binding to lumenal glycoepitopes, and directs both the ubiquitination response and AMPK activation. Proteomic analyses have revealed increased LGALS9 association with lysosomes, and concomitant changes in LGALS9 interactions with its newly identified partners that control ubiquitination-deubiquitination processes. An LGALS9-inetractor, deubiquitinase USP9X, dissociates from damaged lysosomes upon recognition of lumenal glycans by LGALS9. USP9X's departure from lysosomes promotes K63 ubiquitination and stimulation of MAP3K7/TAK1, an upstream kinase and activator of AMPK hitherto orphaned for a precise physiological function. Ubiquitin-activated MAP3K7/TAK1 controls AMPK specifically during lysosomal injury, caused by a spectrum of membrane-damaging or -permeabilizing agents, including silica crystals, the intracellular pathogen Mycobacterium tuberculosis, TNFSF10/TRAIL signaling, and the anti-diabetes drugs metformin. The LGALS9-ubiquitin system activating AMPK represents a novel signal transduction system contributing to various physiological outputs that are under the control of AMPK, including autophagy, MTOR, lysosomal maintenance and biogenesis, immunity, defense against microbes, and metabolic reprograming. Abbreviations: AMPK: AMP-activated protein kinase; APEX2: engineered ascorbate peroxidase 2; ATG13: autophagy related 13; ATG16L1: autophagy related 16 like 1; BMMs: bone marrow-derived macrophages; CAMKK2: calcium/calmodulin dependent protein kinase kinase 2; DUB: deubiquitinase; GPN: glycyl-L-phenylalanine 2-naphthylamide; LLOMe: L-leucyl-L-leucine methyl ester; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MAP3K7/TAK1: mitogen-activated protein kinase kinase kinase 7; MERIT: membrane repair, removal and replacement; MTOR: mechanistic target of rapamycin kinase; STK11/LKB1: serine/threonine kinase 11; TNFSF10/TRAIL: TNF superfamily member 10; USP9X: ubiquitin specific peptidase 9 X-linked